Pembuatan Patung Naga Nusa Nipa sebagai Simbol Pulau Flores Menggunakan Bahan Alam (Daun Lontar) - Alexius Boer; Claudio Geovani Da Rato; Yoseph Esternus Ropi; Siprianus Wangge; Florensius Nong Alpriyadi; Yoseph Freinandemens Ngera; Theresia Alvina Lebi; Charolina Wahyuni Banik (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This article reviews the process of making the Naga Nusa Nipa statue as a cultural symbol of Flores Island, which combines traditional art with the use of environmentally friendly natural materials, namely palm leaves. The Naga Nusa Nipa, as a mythological representation of the Flores community, has a deep meaning in the spiritual and social life of the local community. The creation of this sculpture aims to explore and preserve local cultural values, as well as introduce the uniqueness of Flores Island in the form of fine art. Palmyra leaves were chosen as the main material due to their abundant availability in the area and their functional and aesthetic value. The process of making the sculpture includes the techniques of selecting, processing, and assembling palm leaves into the form of a dragon full of symbolism. The results of this research are expected to contribute to the development of traditional Flores handicrafts and become a medium for education and promotion of local culture for the younger generation and tourists. Thus, the Naga Nusa Nipa statue becomes a symbol that not only elevates Flores culture, but also supports the preservation of natural materials that have the potential to be further developed in the creative industry.